Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2019)
A dataset containing 61227 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "Month is April", "Month is May", "Month is August", "Month is September" ] }, "Year 2008-2019", "HasCoordinate is true", "TaxonKey is Solidago L.", "HasGeospatialIssue is false" ] } The dataset includes 61227 records from 307 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0029668-190918142434337/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences